The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1021/ac011198o
|View full text |Cite
|
Sign up to set email alerts
|

Mass Transfer and Flow in Electrically Charged Micro- and Nanochannels

Abstract: In this work, the fluid flow and mass transfer due to the presence of an electric field in a rectangular channel is examined. We consider a mixture of water or another neutral solvent and a salt compound, such as sodium chloride, for which the ionic species are entirely dissociated. Results are produced for the case in which the channel height is much greater than the electric double layer (EDL) (microchannel) and for the case in which the channel height is of the order of the width of the EDL (nanochannel). B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
90
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(96 citation statements)
references
References 17 publications
(23 reference statements)
3
90
0
Order By: Relevance
“…When the diameter of the pore is small compared to the EDL, the situation is theoretically more complex. In this case, v eo varies across the diameter of the tube, never reaching the value obtained in a wide tube, and as a consequence the overall flow rate is greatly reduced (15). Difficulties in estimating have led to approaches that relate the measured current rather than the applied potential to solvent flow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the diameter of the pore is small compared to the EDL, the situation is theoretically more complex. In this case, v eo varies across the diameter of the tube, never reaching the value obtained in a wide tube, and as a consequence the overall flow rate is greatly reduced (15). Difficulties in estimating have led to approaches that relate the measured current rather than the applied potential to solvent flow.…”
Section: Discussionmentioning
confidence: 99%
“…For example, electroosmosis has been used to produce solvent flow through channels in microfluidic systems, which range from a few to several hundred micrometers in diameter (11)(12)(13). In these systems, the electrical double layer (EDL) is small compared to the diameter of the channel, generating convective plug flow (14,15) that includes dissolved neutral molecules. Despite its apparent simplicity, the theoretical basis of electroosmotic flow in relatively wide channels remains under active discussion and experimental evaluation (16)(17)(18)(19).…”
mentioning
confidence: 99%
“…͑52͒ are compared in Fig. 14͑a͒ for different ionic strengths ͑Qu and Conlisk et al, 2002;Conlisk, 2005͒. It is known that the DebyeHückel approximation generally overestimates the electric potential.…”
Section: Model Of the Exclusion-enrichment Effectmentioning
confidence: 99%
“…Karlsson et al [10] have presented fluidic control in lipid nanotubes 50-150 nm in radius, conjugated with surface immobilized unilamellar lipid bilayer vesicles (5-25 mm in diameter). Conlisk et al [11] have examined the fluid flow and mass transfer under an electric field in a rectangular microchannel and nanochannel. In fact, as early as middle 1960s, Burgreen et al [12] had already reported a similar study of electrokinetic flow (EKF) in very fine capillary channels of rectangular cross section, just like those channels in chips nowadays, which was a natural extension of the general theory of EKF.…”
Section: Introductionmentioning
confidence: 99%